PLANNING ON HATCHING TIME OF GROUPER EGGS THROUGH DIFFERENT INCUBATION TEMPERATURES - Regina Melianawati; Philip Teguh Imanto; Made Suastika (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Groupers were known as a high economically marine commodity and in order to support groupers production, the seed availability was the most important. Eggs are still as limited factor in hatchery production, for this reason the success of eggs transportation is one as base of successful production of seed. Planning on hatching time of eggs through different incubation temperature was an option to solve that problem. This experiment was aimed to find out the optimum temperature for groupers eggs and the minimum temperature to arrange incubation time and to plan the hatching time. Fertilized eggs were incubated into three beaker glasses of 1 liter in volume with the density of ± 250 eggs/liter. The incubation was done under laboratory condition at controlled temperature, i.e. (A) 21-22 ºC, (B) 24-25 ºC, (C) 27-28 ºC and (D) 30-31 ºC. The eggs that used were including orange spotted grouper (Epinephelus coiodes), brown marbled grouper (E. microdon), tiger grouper (E. fuscoguttatus) and humpback grouper (Cromileptes altivelis). Investigated variables were embryonic development pattern, incubation time and hatching rate. The result showed that the eggs incubated in temperature range of 24-31°C had the normal sequence of embryonic development pattern, but in temperature of 21-22°C performed irregular sequence and the embryonic development stopped at blastula or gastrula stage or even the eggs could still develop but the body of hatched larvae were abnormal. In lower temperature incubation, the incubation time was longer and the hatching rate of eggs was lower than those in higher temperature. Therefore the optimum temperature for incubation of orange spotted grouper, marbled grouper, tiger grouper and humpback grouper eggs ranged between 24-31 ºC, while the lowest possible temperature was 24 ºC.Keywords: incubation temperature, embryonic development pattern, grouper eggs, hatching rate